Species Diversity and Molecular Phylogeny of Cyanosporus (Polyporales, Basidiomycota) - Liu, Shun; Shen, Lu-Lu; Wang, Yan; Xu, Tai-Min; Gates, Genevieve; Cui, Bao-Kai (Frontiers in Microbiology, 2021)
Cyanosporus is a cosmopolitan brown-rot fungal genus, recognizable by blue-tinted basidiocarps. Species in this genus were usually treated as belonging to the Postia caesia complex, however, recent phylogenetic analyses showed that this complex represents an independent genus. During further studies on Cyanosporus, five new species were discovered based on morphological features and molecular data. Phylogenetic analyses of Cyanosporus were conducted using the internal transcribed spacer (ITS) regions, the large subunit of nuclear ribosomal RNA gene (nLSU), the small subunit of nuclear ribosomal RNA gene (nSSU), the small subunit of mitochondrial rRNA gene (mtSSU), the largest subunit of RNA polymerase II (RPB1), the second largest subunit of RNA polymerase II (RPB2), and the translation elongation factor 1-α gene (TEF); illustrated descriptions of the new species are provided. In addition, fifteen species previously belonging to the Postia caesia complex are transferred to Cyanosporus and proposed as new combinations.